2015
DOI: 10.1097/iae.0000000000000574
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Findings and Surgical Outcomes of Tissue Plasminogen Activator–assisted Vitrectomy for Submacular Hemorrhage Secondary to Age-Related Macular Degeneration

Abstract: The preoperative presence of detectable ellipsoid layers and a lower height of SMH may predict good visual prognosis. In contrast, no specific features of pigment epithelial detachment correlated with postoperative best-corrected visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
1
12
3
Order By: Relevance
“…As this was only noted in univariate analysis, we suggest further study is needed and that IVB combined with PD may have a role in treating patients in the outpatient clinic. In contrast to previous studies suggesting the integrity of the IS/OS line and SMH height as good indicators for long‐term visual outcome, our study found no significance …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As this was only noted in univariate analysis, we suggest further study is needed and that IVB combined with PD may have a role in treating patients in the outpatient clinic. In contrast to previous studies suggesting the integrity of the IS/OS line and SMH height as good indicators for long‐term visual outcome, our study found no significance …”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previous studies suggesting the integrity of the IS/OS line and SMH height as good indicators for long-term visual outcome, our study found no significance. 20 Although complications such as sudden retinal detachment and breakthrough VH in nonvitrectomized eyes receiving PD have been previously reported, 19 there were no occurrences of retinal detachment or other significant complications associated with the use of PD in our study.…”
Section: Discussionmentioning
confidence: 44%
“…Hirashima et al . [33] recently reported that there was a significant relationship between a better postoperative BCVA and SMH height <400 milimicron. This report is the only one to evaluate vertical height and OCT findings of SMHs.…”
Section: Discussionmentioning
confidence: 99%
“…[222223224225] The visual outcome depends on presenting BCVA, the duration, thickness, extent of hemorrhage, thinner neurosensory retinal thickness at presentation, and disruption of ellipsoid zone. [226227228229230231] The aim of treatment is to displace the hemorrhage before irreversible damage to photoreceptors occurs. SMH secondary to PCV is treated with pneumatic displacement or vitrectomy with pneumatic displacement.…”
Section: Treatment Of Submacular Hemorrhagementioning
confidence: 99%